Survey on wireless body area sensor networks for healthcare applications: Signal processing, data analysis and feedback - Al-Saud, Khalid Abu; Mohamed, Amr; Mahmuddin, Massudi (2011)
Wireless sensor networks (WSNs) technologies are considered as one of the key of the research areas in computer science and healthcare application industries.The wireless body area sensor networks (WBASNs) is a wireless network used for communication among sensor nodes operating on or inside the human body in order to monitor vital body parameters and movements.The paper surveys the state-of-the-art on WBASNs discussing the major components of research in this area including physiological sensing, data preprocessing, detection and classification of human related phenomena. We provide comparative studies of the technologies and techniques used in such systems.